오령산의 고혈압 치료 효과에 대한 체계적 고찰 : 임상 논문을 중심으로 - 이혜윤; 강기완; 이은; 이승호; 한창호; 장인수; Lee, Hye-Yoon; Kang, Ki-Wan; Lee, Eun; Lee, Seung-Ho; Han, Chang-Ho; Jang, In-Soo (대한한방내과학회지, 2013)
Objectives : The purpose of this study was to review the clinical studies on antihypertensive effects of Oryeong-san. Methods : We searched papers using KTKP, Oasis, CNKI, PubMed, Embase, Science Direct, CINAHL, J STAGE and CiNii, and the key words "Oryeong-san (韓)", "Wuling-san (中)", "Gorei-san (日)", and "Hypertension" were used. Search range included randomized controlled trials (RCTs), clinical reports, reviews and animal experiments. Papers not matched with inclusion criteria were excluded. Results : A total 479 studies were found, with 457 excluded during title and screening. After scanning 22 papers, a final 3 RCTs and 6 case reports were selected and analyzed. In the 3 RCTs, the number of patients varied between 65 and 156. Patients with hypertension were randomized into groups for treatment group and control group. They were all treated with antihypertensive drugs (Vamlodipine Besylate, Benazepril, Perindopril); the treatment group was also given modified Oryeong-san. After treatment, results were that blood pressure was significantly decreased in the treatment group, compared to the control. The other 6 case reports reported that modified Oryeong-san alone or the combination of Oryeong-san plus antihypertensive drugs had beneficial effects on blood pressure. Conclusions : Oryeong-san appears to be effective in improving blood pressure and hypertension-related symptoms. The results of this study could be applied to clinical treatment of hypertension. Further large-scale clinical researches should be conducted.